New Plants for Florida: Tropical Fruit - Alan H. Chambers; Jonathan H. Crane; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
Florida tropical fruit industry acreage has fluctuated during the past 70 years due to natural disasters, foreign competition and changes in the U.S. demographics. Today, there are about 16,000 acres in cultivation, with an economic impact of over $137 million annually. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.